Combining in situ proteolysis and mass spectrometry to crystallize Escherichia coli PgaB - Little, Dustin J. (International Union of Crystallography, 2012)
The periplasmic poly-β-1,6-N-acetyl-d-glucosamine (PNAG) de-N-acetylase PgaB from Escherichia coli was overexpressed and purified, but was recalcitrant to crystallization. Use of the in situ proteolysis technique produced crystals of PgaB, but these crystals could not be optimized for diffraction studies. By analyzing the initial crystal hits using SDS–PAGE and mass spectrometry, the boundaries of the protein species that crystallized were determined. The re-engineered protein target crystallized reproducibly without the addition of protease and with significantly increased crystal quality. Crystals of the selenomethionine-incorporated protein exhibited the symmetry of space group P2(1)2(1)2(1) and diffracted to 2.1 Å resolution.